Micro CT Analysis of Spine Architecture in a Mouse Model of Scoliosis - Gao, Chan; Chen, Brian P.; Sullivan, Michael B.; Hui, Jasmine; Ouellet, Jean A.; Henderson, Janet E.; Saran, Neil (Frontiers in Endocrinology, 2015)
Objective: Mice homozygous for targeted deletion of the gene encoding fibroblast growth factor receptor 3 (FGFR3-/-) develop kyphoscoliosis by two months of age. The first objective of this study was to use high resolution X-ray to characterize curve progression in vivo and micro CT to quantify spine architecture ex vivo in FGFR3-/- mice. The second objective was to determine if slow release of the bone anabolic peptide parathyroid hormone related protein (PTHrP 1-34) from a pellet placed adjacent to the thoracic spine could inhibit progressive kyphoscoliosis. Materials and Methods: Pellets loaded with placebo or PTHrP 1-34 were implanted adjacent to the thoracic spine of one month old FGFR3-/- mice obtained from in house breeding. X rays were captured at monthly intervals up to four months to quantify curve progression using the Cobb method. High resolution post-mortem scans of FGFR3-/- and FGFR3+/+ spines, from C5/6 to L4/5 were captured to evaluate the 3D structure, rotation and micro-architecture of the affected vertebrae. Un-decalcified histology was performed on the apical and adjacent vertebrae of FGFR3-/- spines, and the corresponding vertebrae from FGFR3+/+ spines. Results: The mean Cobb angle was significantly greater at all ages in FGFR3-/- mice compared with wild type mice and appeared to stabilize around skeletal maturity at four months. 3D reconstructions of the thoracic spine of four month old FGFR3-/- mice treated with PTHrP 1-34 revealed correction of left/right asymmetry, vertebral rotation and lateral displacement compared with mice treated with placebo. Histologic analysis of the apical vertebrae confirmed correction of the asymmetry in PTHrP 1-34 treated mice, in the absence of any change in bone volume, and a significant reduction in the wedging of intervertebral discs (IVD) seen in placebo treated mice. Conclusion: Local treatment of the thoracic spine of juvenile FGFR3-/- mice with a bone anabolic agent inhibited progression of scoliosis